Surgical Strategy in Patients with Complete Transposition of Internal Organs in Cancer of the Biliopancreatoduodenal Zone - R. V. Ischenko; Yu. V. Ivanov; A. V. Smirnov; V. N. Antipov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to present two clinical cases of successful surgical treatment of patients with a combination of complete transposition of internal organs and cancer of the biliopancreatoduodenal zone.Key points. A 65-year-old man underwent gastropancreatoduodenal resection for cancer of the large duodenal papilla. In addition to the situs vicserum inversus, this patient revealed a special variant of vascular anatomy, namely: separate separation of the left and right hepatic arteries from the ventral trunk. A 70-year-old man, in addition to complete transposition of internal organs, had a combination of cancer of the terminal part of the common bile duct and heterotaxy syndrome in the form of polysplenia, aplasia of the hepatic segment of the inferior vena cava, agenesis of the dorsal pancreatic rudiment (“short” pancreas), intrapancreatic course of the right hepatic artery extending from the superior mesenteric arteries, rotational abnormalities of intestinal development. This patient underwent a total pancreatectomy. In both cases, the main difficulties in mobilizing the pancreatoduodenal complex arose due to anatomical disorientation and the absence of standard (familiar) topographic and anatomical landmarks for the surgeon.Conclusion. In all patients with tumors of the biliopancreatoduodenal zone, a detailed assessment of the vascular anatomy of this area is required before surgery, with the study of the course of the main visceral vessels and their large branches using multispiral computed tomography in vascular mode. If heterotaxy syndrome is suspected, additional examination is necessary to identify hidden developmental anomalies, which allows surgeons to be prepared for an unusual situation. Gastropancreatoduodenal resection or total pancreatectomy in situs viscerum inversus is a technically complex intervention and should be performed in large multidisciplinary medical institutions, and the operating team should have extensive experience in operations on the organs of the biliopancreatoduodenal zone.